2018
DOI: 10.1088/1741-2552/aae493
|View full text |Cite
|
Sign up to set email alerts
|

Spike-triggered average electrical stimuli as input filters for bionic vision—a perspective

Abstract: Spike-triggered average electrical stimuli as input filters for bionic vision-a perspective.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 113 publications
(154 reference statements)
1
27
1
Order By: Relevance
“…System identification approaches to estimate preferred stimuli of neurons are always limited to finding the preferred stimulus within the subspace that is spanned by the presented stimuli; if the true preferred stimulus ) between predicted and true firing rate at a resolution of 1 kHz, evaluated separately for the three identified clusters among wt filters, as well as for rd10 filters. (2020) 10:5248 | https://doi.org/10.1038/s41598-020-61899-y www.nature.com/scientificreports www.nature.com/scientificreports/ is not in this subspace, it can only be approximated by the most closely matching stimulus within the subspace that was sampled 35,49 . Our smooth electrical stimulus broadly, but certainly not exhaustively, samples stimulus space, simultaneously probing different stimulus dimensions like frequency, amplitude and polarity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…System identification approaches to estimate preferred stimuli of neurons are always limited to finding the preferred stimulus within the subspace that is spanned by the presented stimuli; if the true preferred stimulus ) between predicted and true firing rate at a resolution of 1 kHz, evaluated separately for the three identified clusters among wt filters, as well as for rd10 filters. (2020) 10:5248 | https://doi.org/10.1038/s41598-020-61899-y www.nature.com/scientificreports www.nature.com/scientificreports/ is not in this subspace, it can only be approximated by the most closely matching stimulus within the subspace that was sampled 35,49 . Our smooth electrical stimulus broadly, but certainly not exhaustively, samples stimulus space, simultaneously probing different stimulus dimensions like frequency, amplitude and polarity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, investigating network-mediated electrical activation of rat RGC, ON cells were found to prefer anodic-first biphasic pulses, and OFF cells to prefer cathodic-first pulses, but the difference in preference was small 39 . Antagonistic polarities of electrical filters in wild-type mouse ON and OFF cells have been reported as well 41 ; however, the clinical applicability of these filters as stimuli is limited as they most likely arose due to photoreceptor activation 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, investigating network-mediated electrical activation of rat RGC, ON cells were found to prefer cathodic-first biphasic pulses, and OFF cells to prefer anodic-first pulses, but the difference in preference was small 33 . Antagonistic polarities of electrical filters in wild-type mouse ON and OFF cells have been reported as well 35 ; however, the clinical applicability of these filters as stimuli is limited as they most likely arose due to photoreceptor activation 40 . In this study, we found three different classes of RGC filters in response to smooth electrical stimulation in wild-type, and one class of filter in photoreceptor-degenerated mouse retina.…”
Section: Discussionmentioning
confidence: 99%
“…This distortion is caused by the activation of the axon of passages, which is a main limitation of epi-retinal prostheses. However, several approaches were recently reported to overcome the direct activation of retinal ganglion cells and favour the network-medicated activation, mainly based on waveform shaping [34,35] and input filters [36]. In humans, it was also demonstrated that long sinusoidal-like pulses promote the perception of circular phosphenes [37].…”
Section: Discussionmentioning
confidence: 99%